Co-torrefaction of corncob and waste cooking oil coupled with fast co-pyrolysis for bio-oil production. (February 2023) - Wu, Qiuhao; Zhang, Letian; Ke, Linyao; Zhang, Qi; Cui, Xian; Fan, Liangliang; Dai, Anqi; Xu, Chuangxin; Zhang, Qihang; Bob, Krik; Zou, Rongge; Liu, Yuhuan; et al.
Graphical abstract: Highlights: A new idea for hydrocarbon production by co-torrefaction coupled with co-pyrolysis. Hydrogen in oil-bath co-torrefied corncob increased from 5.21 wt% to 6.12 wt%. Average activation energy of oil-bath co-torrefied corncob was 164.29 kJ/mol. Oil-bath co-torrefaction residual was more suitable for bio-oil production. Torrefaction temperature has the greatest effect on pyrolysis bio-oil composition. Abstract: Lignocellulosic biomass is a rich source of fixed renewable carbon and a promising alternative to fossil sources. However, low effective hydrogen to carbon ratio limits its applications. This work studied the influence of oil-bath co-torrefaction of corncob and waste cooking oil for co-pyrolysis. It was compared with dry torrefaction and hydrothermal wet torrefaction firstly. Residual of oil-bath co-torrefaction were the highest of 97.01 %. Oil-bath co-torrefaction could maximize hydrogen atoms retention in corncob, which has a positive significance for deoxygenation during pyrolysis. Oil-bath co-torrefaction could also reduce the average activation energy required for corncob decomposition, while it was increased with dry torrefaction. Oil-bath co-torrefaction coupled with co-pyrolysis was more suitable for hydrocarbon-rich bio-oil production. Oil-bath co-torrefaction temperature had the greatest influence on bio-oil composition. High pressure promoted formation of the CC double bond and degradation of lignin, which further promoted the formation of monocyclic aromatics in bio-oil.